Heavy Metal Contamination and Its Effects on Ecosystems and Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint showcases recent advances on heavy metal contamination across soil, water, sediments, air, and the food chain, with a focus on risks to ecosystems and human health as well as practical solutions. Contributors quantify exposure pathways and bioaccumulation, refine human health risk assessment, and link chemistry to biological effects using modern analytics and data-driven methods. Studies compare regulatory thresholds with real-world concentrations, highlight spatial and temporal monitoring strategies, and examine co-occurring stressors such as organic pollutants and microplastics. A major emphasis is on remediation and safe utilization. Papers evaluate physical removal, chemical stabilization, and emerging green technologies, including phytoremediation, microbial processes, engineered amendments, and circular approaches that recover resources while lowering toxicity. Case studies report field scale performance, life cycle considerations, and cost effectiveness, offering decision-ready evidence for practitioners and policy makers. Together, this Reprint provides a current, integrated view of heavy metal pollution and actionable routes to prevention, cleanup, and risk reduction.